Influence of the depth of intraradicular dentin on the pushout bond strength of resin materials - Yumi Umeda Suzuki, Thaís [UNESP]; Gomes-Filho, João Eduardo [UNESP]; Fraga Briso, André Luiz [UNESP]; Gonçalves Assunção, Wirley [UNESP]; Dos Santos, Paulo Henrique [UNESP] (Wiley, 2019)
AIM: The aim of the present study was to evaluate the pushout bond strength between glass-fiber posts to different regions of intraradicular dentin with different materials for adhesive cementation. METHODS: After endodontic filling, 40 teeth were divided into five groups according to adhesive cementation: Adper Single Bond 2 + RelyX ARC, Excite DSC + RelyX ARC (EXC), Adper SE Plus + RelyX ARC (SEP), RelyX Unicem, and Set. After the bonding process, roots were sectioned obtaining slices to be analyzed from each third. The bond strength was measured using the pushout test in a universal testing machine (Emic DL 3000) at a cross-head speed of .5 mm/minutes in different areas of the post space (cervical, middle, and apical). Data were subjected to analysis of variance and Fisher's test (α = .05). RESULTS: The highest values for the pushout bond strength were found for the SEP group in all experimental conditions, without a significant difference for the EXC group in the middle and apical regions. There was a decrease in pushout bond strength in the cervical-apical direction for all groups, except the EXC group, which did not show a difference among the different regions. CONCLUSIONS: The different interactions of the resin materials and the intraradicular depth influenced the bond strength of adhesives materials to dentin substrate.
Keywords: adhesive; dentin; polymerization; pushout strength; resin cement